ERROR ANALYSIS ON STUDENTS WRITING TASK OF PERSONAL LETTERS - Ma```la, Shofwatul; Ambarini, Ririn (MARAS : Jurnal Penelitian Multidisiplin, 2023)
This study tries to classify and explain the many types of writing errors that were discovered in students' personal letters. The outcomes are ascertained by a qualitative data analysis employing the writing assignments of the students as the source of data. The Surface Strategy Taxonomy is used to pinpoint the errors. The researcher employs comparative analysis to divide the students into several skill levels when gathering data. The goal of this study is to identify mistakes committed by science-majoring eleventh-graders at SMAN 6 Kota Semarang, who number 36 students, in their personal letter assignment. The total of errors are 274 errors were classified in this study, with omission errors (f=131, 47.81%) as the most common. The second commonplace fault category was mis-formation errors (f=127, 46.35%). These categories were followed by addition error (f=9, 3.28%) and mis-order error (f=7, 2.55%). From the above result, we can conclude that the most prevalent mistakes among the learners is omission where they frequently eliminate sort of parts which needed in the full sentences due to the fact lack of English grammar knowledge.